Evaluate the effect of the metranidazole gel on healing of partial thickness flap in rats (serum TNF-a) (Mustansiria Dental Journal, 2024)
Background: Metronidazole is a broad-spectrum antimicrobial activity against protozoan infections and anaerobic bacteria. In the late 1950s, Metronidazole was first introduced for the treatment of trichomoniasis. At present, the antimicrobial metronidazole is one of the most widely used as antibacterial compounds in the treatment of periodontal disease 9. Beside the periodontal pocket debridement (subgingival scaling and curettage), topical application of metronidazole seems to be very efficacious. Metronidazole efficiently inhibited anaerobic microorganisms in the periodontal pockets 10.Objective: Evaluating the effect of metronidazole gel into surgically healing process of the partial thickness flap, throughout immunological study and comparing it with the chlorhexidine gelAnimals and methods: The present study was carried out in Hawler Medical University, Medical research center, College of DentistryChemicals and Reagents:- (Rat TNF-a ELISA) kit for estimation of serum tumor necrosis factor (TNF-a), KOMA BIOTECH INC. USA)